Evaluation of Village Fund Allocation on Indonesia - Anik Puji Handayani; Rudy Badrudin (Universitas Muhammadiyah Yogyakarta, Indonesia, 2019)
This study focuses on evaluation on Village Fund Allocation through on examining the effect of the Village Fund Allocation on Capital Expenditure, Economic Growth, Poverty, and Social Welfare. Using secondary data and purposive sampling method, this study has 411 districts as the samples with criteria in 2015. This study used Partial Least Square (PLS) to predict relationships between variables. Before doing the analysis of PLS, Klassen typology analysis was conducted. In Klassen typology, the districts in Indonesia were grouped into 4 quadrants, namely quadrant I (developing area), quadrant II (prime area), quadrant III (potential area), and quadrant IV (backward area). PLS test results (using a sample of districts throughout Indonesia) indicate that all hypotheses are not supported. Whereas in the classification of Klassen typology (using samples in each quadrant) only in certain quadrants a hypothesis is supported. This shows that the Village Fund Allocation has not had a significant impact on the economy of the Indonesian people.